Hydrodynamic quality factor as an objective quantitative characteristic of assessment of swimming technique - Dyshko, B. A.; Kochergin, A. B. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Stroke efficiency is determined by its compliance with solvable tasks and high final result, level of athlete's physical, tactical and psychological skills. Stroke efficiency is estimated and controlled in real training and competitive exercises using the methodology estimating the travel speed of the common center of mass of athlete's body (CCMAB) or the methodology of evaluation of the dynamics of closed cycle speed [1,2,5-7]. Closed cycle speed (CCS) of CCMAB travel is characterised by Vmax,m/s- maximal values of swimming CCS in one cycle, Vm;n, m/s- minimal value of swimming CCS in one cycle and alternation of acceleration and inhibitory phases (Fig. 1). CCS of CCMAB in swimming is known [2, 5-7] to change according to the quasiperiodic law, providing the opportunity to involve some conditions of mathematical apparatus of the vibration theory to estimate stroke efficiency in real movements (3]. The energy efficiency of the quasiperiodic process is estimated by the quality of the oscillating system Q. Quantitatively the quality Q is equal to the ratio of energy saved in the system and the value of energy lost in one period of oscillations, multiplied by 2n: [4]. The quality of the quasiperiodic process we study can be determined using the above mentioned definition of the quality of oscillating system as a ratio of energy saved in the system and energy used within one period of oscillations (without regard of the constant factor 2rr). Since energy is definitely related to the squared travel velocity, in our case quality is equal to K=Vmax^2/(Vmax^2-Vmin^2) where: Vmax, m/s-maximum CCS in one swimming cycle; Vmin, m/s-minimum CCS in one swimming cycle. We called the obtained characteristics 'hydrodynamic quality coefficient' (HQC) or hydrodynamic quality Q. lt is known [2, 6] that stroke is more efficient when the difference between Vmax and Vmin is smaller. So, the less different Vmax and V m in are, the higher HQC is, the less energy is required to maintain the high average speed of swimming, the more effective athlete's stroke is. The aim of research was the development and the approbation of the biomechanical characteristics for a quantitative assessment of swimming technique from of the energy efficiency position